A comparison of the cushioning effect of a popular running shoe and a shoe using a new spring technology during running - Flores, M.; Smith, M. S.; Smith, D. R. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
The purpose of the study was to compare the cushioning effect of the Nike Air Pegasus 2004 and the Spira Volare IITM during running. Measured variables were peak force, peak force relative to body weight and time-to-peak force. It was determined that time-topeak force was not significantly different (p=0.1745) between the Spira and the Nike. There were significant differences found in peak force values (p=0.0184) with Nike exhibiting higher forces than Spira. Peak forces normalized to body weight exhibited a significant shoe by gender interaction (p=0.032). Further analysis revealed the Nike had significantly higher forces than the Spira for females (p=0.0048) but not for males (p=0.8544). It was concluded that the Spira Volare II is similar to the Nike Air Pegasus 2004 in time-to-peak force but significantly lower in peak forces, particularly for females.